Collective Trauma and Psychological Insecurity: Obstacles to Peace in the Israel-Palestine Conflict - Farabi, Nadia (Department of International Relations, Universitas Brawijaya, 2025)
The Israel-Palestine conflict, one of the most enduring intractable conflicts, is shaped not only by political and economic factors but also by the psychological impact of collective trauma. This study explores how collective trauma, deeply embedded within group identities, reinforces patterns of mistrust and hostility between communities. Using a qualitative literature review, the research examines the influence of collective trauma on psychological resilience and human security, analysing how intergenerational transmission of traumatic narratives hinders reconciliation efforts. Data was collected from scholarly journals, books, and international reports and analysed using content analysis to identify key themes surrounding collective trauma’s role in sustaining conflict dynamics. Findings highlight collective trauma as a barrier to psychological recovery and a critical factor in the ongoing security challenges faced by both communities. The study contributes to conflict resolution strategies by emphasising the need for trauma-informed peacebuilding interventions.